2016
DOI: 10.15252/embr.201541438
|View full text |Cite
|
Sign up to set email alerts
|

Expression of A152T human tau causes age‐dependent neuronal dysfunction and loss in transgenic mice

Abstract: A152T‐variant human tau (hTau‐A152T) increases risk for tauopathies, including Alzheimer's disease. Comparing mice with regulatable expression of hTau‐A152T or wild‐type hTau (hTau‐WT), we find age‐dependent neuronal loss, cognitive impairments, and spontaneous nonconvulsive epileptiform activity primarily in hTau‐A152T mice. However, overexpression of either hTau species enhances neuronal responses to electrical stimulation of synaptic inputs and to an epileptogenic chemical. hTau‐A152T mice have higher hTau … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
93
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 102 publications
14
93
0
Order By: Relevance
“…The natural behavior of nest building in mice has been used to assess impairment with AD and tauopathy (Torres-Lista and Gimenez-Llort, 2013, Maeda et al, 2016) and can be quantified based on published criteria (Figure 3A). Compared to male hTau mice treated with either saline or scrambled ASO (n=4), hTau mice given 3R to 4R splicing ASO (n=5) exhibited significantly lower nestlet scores (p<0.05; Figure 3B) and greater weights of untorn nestlet (p<0.05; Figure 3C), implicating increased 4R-tau in impaired nesting ability.…”
Section: Resultsmentioning
confidence: 99%
“…The natural behavior of nest building in mice has been used to assess impairment with AD and tauopathy (Torres-Lista and Gimenez-Llort, 2013, Maeda et al, 2016) and can be quantified based on published criteria (Figure 3A). Compared to male hTau mice treated with either saline or scrambled ASO (n=4), hTau mice given 3R to 4R splicing ASO (n=5) exhibited significantly lower nestlet scores (p<0.05; Figure 3B) and greater weights of untorn nestlet (p<0.05; Figure 3C), implicating increased 4R-tau in impaired nesting ability.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, the A152T mutation lies far outside the repeat domain and has only a weak effect on tau aggregation, and its role as a risk factor in FTD spectrum disorders or AD is still poorly understood. The different effects of both mutations have been further demonstrated by comparing the phenotype of P301L (Lin et al ., 2003) and the novel tau‐A152T transgenic mouse models (Decker et al ., 2016; Maeda et al ., 2016; Sydow et al ., 2016). However, the basis for these phenotypic differences is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…S6, Supporting information). The different impact of both mutations in the autophagic degradation of tau goes in line with the severity of tau toxicity in the mouse models expressing copies of these proteins (Lin et al ., 2003; Decker et al ., 2016; Maeda et al ., 2016; Sydow et al ., 2016). Pathology and tau aggregation in mouse expressing the Tau‐A152T mutation occur at a slower pace than in the tau‐P301L overexpressor, where tangles appear as early as 4.5 month (Lin et al ., 2003) and where we found a more severe impairment of its autophagic degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies demonstrated that premature death is closely associated with spontaneous seizures and abnormal epileptiform electroencephalography (EEG) activities [39, 40]. The implicated contribution of amyloid peptides and/or APP metabolites, alone and even more when combined with mutant protein tau [41], in inducing neuronal hyperexcitability and epilepsy susceptibility is evident. These animal model observations are consistent with the higher incidence of epileptic activity in aged AD patients as compared to non-dementing elderly [42].…”
Section: Discussionmentioning
confidence: 99%